New evidence on taxes and portfolio choice - Sule Alan; Kadir Atalay; Thomas F. Crossley; Sung-hee Jeon (Institute for Fiscal Studies (IFS), 2009)
Identifying the effect of differential taxation on portfolio allocation requires exogenous variation in marginal tax rates. Marginal tax rates vary with income, but income surely affects portfolio choice directly. In systems of individual taxation - like Canada's - couples with the same household income can face different effective tax rates on capital income when labor income is distributed differently within households. Using this source of variation we find statistically significant but economically modest responses to taxation. In a placebo' test, using data from the U.S. (which has joint taxation), we find no effect of the intra-household distribution of labor income on portfolios.
Keywords: G11; H24; H31; 330; Household Portfolio Choice; Taxes; Portfolio-Management; Privater Haushalt; Einkommensteuer; Kapitalertragsteuer; Kanada; USA